Causes of death in Japanese patients with diabetes based on the results of a survey of 45, 708 cases during 2001–2010: Report of the Committee on Causes of Death in Diabetes Mellitus. Issue 3 (27th March 2017) - Nakamura, Jiro; Kamiya, Hideki; Haneda, Masakazu; Inagaki, Nobuya; Tanizawa, Yukio; Araki, Eiichi; Ueki, Kohjiro; Nakayama, Takeo
Abstract : The principal causes of death among 45, 708 patients with diabetes (29, 801 men and 15, 907 women) who died in 241 hospitals throughout Japan during 2001–2010 were determined based on a survey of the hospital records. The most frequent cause of death was malignant neoplasia, followed, in order of descending frequency, by infections and then vascular diseases, including renal failure, ischemic heart diseases and cerebrovascular diseases. Abstract: The principal causes of death among 45, 708 patients with diabetes (29, 801 men and 15, 907 women) who died in 241 hospitals throughout Japan during 2001–2010 were determined based on a survey of the hospital records. Autopsy had been conducted in 978 of the 45, 708 cases. The most frequent cause of death was malignant neoplasia (38.3%), followed by, in order of descending frequency: infections (17.0%); and then vascular diseases (14.9%), including renal failure (3.5%), ischemic heart diseases (4.8%) and cerebrovascular diseases (6.6%). Diabetic coma associated with hyperglycemia with or without ketoacidosis accounted for only 0.6% of the deaths. In regard to the relationship between the age and cause of death in patients with diabetes, the incidence of death due to vascular diseases was higher in patients over the age of 30 or 40 years, and the 97.0% of the total death due to vascular diseases was observed in patients over the age of 50 years. The incidence of death due to infectious diseases, especially pneumonia, increased in an age‐dependent fashion, and the 80.7% of the total death due to pneumonia was observed in patients over the age of 70 years. 'Poorer' glycemic control was associated with the reduced lifespan of patients with diabetes, especially of those with nephropathy. The average age at death in the survey population was 72.6 years. The lifespan was 1.6 years shorter in patients with 'poorer' glycemic control than in those with 'better' glycemic control. In patients with diabetes of less than 10 years' duration, the incidence of death due to macroangiopathy was higher than that due to nephropathy. Of the 45, 708 patients with diabetes, 33.9% were on oral medication, 41.9% received insulin therapy and 18.8% were treated by diet alone. Among the patients in whom the cause of death was diabetic nephropathy, a high percentage, 53.7%, was on insulin therapy. The average age at death of the 45, 708 patients with diabetes was 71.4 years in men and 75.1 years in women. However, the report of the Ministry of Health and Welfare of Japan in 2010 set the average lifespan of the Japanese at 79.6 years for men and 86.3 years for women. Thus, the average lifespan of patients with diabetes still appears to be shorter than that of the general population in Japan. However, the differences in lifespan between patients with diabetes and the general population were shorter than those in the former surveys.